Nanoparticle theranostics in cardiovascular inflammation. (August 2021) - MacRitchie, Neil; Di Francesco, Valentina; Ferreira, Miguel Filipe Moreira Marques; Guzik, Tomasz J.; Decuzzi, Paolo; Maffia, Pasquale
Abstract: Theranostics, literally derived from the combination of the words diagnostics and therapy, is an emerging field of clinical and preclinical research, where contrast agents, drugs and diagnostic techniques are combined to simultaneously diagnose and treat pathologies. Nanoparticles are extensively employed in theranostics due to their potential to target specific organs and their multifunctional capacity. In this review, we will discuss the current state of theranostic nanomedicine, providing key examples of its application in the imaging and treatment of cardiovascular inflammation.